One language, two number-word systems and many problems: numerical cognition in the Czech language - Pixner, S; Zuber, J; Heřmanová, V; Kaufmann, L; Nuerk, H-C; Moeller, K (Research in developmental disabilities, 2011)
Comparing numerical performance between different languages does not only mean comparing different number-word systems, but also implies a comparison of differences regarding culture or educational systems. The Czech language provides the remarkable opportunity to disentangle this confound as there exist two different number-word systems within the same language: for instance, "25" can be either coded in non-inverted order "dvadsetpät" [twenty-five] or in inverted order "pätadvadset" [five-and-twenty]. To investigate the influence of the number-word system on basic numerical processing within one culture, 7-year-old Czech-speaking children had to perform a transcoding task (i.e., writing Arabic numbers to dictation) in both number-word systems. The observed error pattern clearly indicated that the structure of the number-word system determined transcoding performance reliably: In the inverted number-word system about half of all errors were inversion-related. In contrast, hardly any inversion-related errors occurred in the non-inverted number-word system. We conclude that the development of numerical cognition does not only depend on cultural or educational differences, but is indeed related to the structure and transparency of a given number-word system.
Keywords: dítě; jazyk (prostředek komunikace); Male; Language; kognice; Students; lidé; Mathematics; Czech Republic; Česká republika; ženské pohlaví; kulturní charakteristiky; psycholingvistika; Memory, Short-Term; Cognition; matematika; mužské pohlaví; krátkodobá paměť; Child; Semantics; studenti; Humans; Cultural Characteristics; Psycholinguistics; sémantika; Female